Oral route lipopolysaccharide as a potential dementia preventive agent inducing neuroprotective microglia - Mizobuchi, Haruka (Frontiers in Immunology, 2023)
In today's aging society, dementia is an urgent problem to be solved because no treatment or preventive methods have been established. This review focuses on oral administration of lipopolysaccharide (LPS), an outer membrane component of Gram-negative bacteria, as a novel preventive drug for dementia. LPS is also called endotoxin and is well known to induce inflammation when administered systemically. On the other hand, although we humans routinely ingest LPS derived from symbiotic bacteria of edible plants, the effect of oral administration of LPS has hardly been studied. Recently, oral administration of LPS was reported to prevent dementia by inducing neuroprotective microglia. Furthermore, it has been suggested that colony stimulating factor 1 (CSF1) is involved in the dementia prevention mechanism by oral administration of LPS. Thus, in this review, we summarized the previous studies of oral administration of LPS and discussed the predicted dementia prevention mechanism. In addition, we showed the potential of oral LPS administration as a preventive drug for dementia by highlighting research gaps and future issues for clinical application development.